2015
DOI: 10.1021/acs.jpcc.5b05393
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on the Growth Mechanism of Methane plus Tetrahydrofuran Mixed Hydrates

Abstract: Molecular dynamics (MD) simulations are performed to analyze the dominating factors for the growth of CH 4 + THF mixed hydrates, and the results are compared with the growth of single guest CH 4 and THF hydrates. While CH 4 hydrate has a type I crystalline structure, the presence of THF in the aqueous phase results in the growth the type II structure hydrate. Compared to THF hydrates, the presence of CH 4 in the system enhances the dissociation temperature. The growth rate of CH 4 + THF mixed exhibits a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Based on computer simulation methods [23], several hypotheses have been proposed to illustrate the microprocess of hydrate nucleation and growth, including a labile cluster hypothesis [24,25], a local structuring hypothesis [26], a blob mechanism [27], and a cage adsorption hypothesis [28]. Further, Wu and coworkers [29] have carried out a molecular dynamics study of the growth of the THF-CH 4 binary hydrate, and found that the growth rate is dominated by the adsorption of CH 4 to the growing interface and the migration and rearrangement of THF at the interface. Alavi and coworkers [30] have studied the hydrogen bonding of THF in binary sII hydrates via molecular dynamics simulations, and suggested that the number and nature of the second guests can affect the probability of hydrogen bonding of THF.…”
Section: Introductionmentioning
confidence: 99%
“…Based on computer simulation methods [23], several hypotheses have been proposed to illustrate the microprocess of hydrate nucleation and growth, including a labile cluster hypothesis [24,25], a local structuring hypothesis [26], a blob mechanism [27], and a cage adsorption hypothesis [28]. Further, Wu and coworkers [29] have carried out a molecular dynamics study of the growth of the THF-CH 4 binary hydrate, and found that the growth rate is dominated by the adsorption of CH 4 to the growing interface and the migration and rearrangement of THF at the interface. Alavi and coworkers [30] have studied the hydrogen bonding of THF in binary sII hydrates via molecular dynamics simulations, and suggested that the number and nature of the second guests can affect the probability of hydrogen bonding of THF.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the simulations are performed in the NPT ensemble at 270 K and 20 MPa (at this stage, all of the molecules of hydrate are free). ,, The total calculation time is 200 ns. The Nosé–Hoover thermostat is used to control the temperature, and the Parrinello–Rahman barostat is used to control the pressure. The temperature and pressure time constants are 4 and 10 ps, respectively. The compressibility is 4.5 × 10 –4 MPa –1 .…”
Section: Calculation Model and Methodsmentioning
confidence: 99%
“…The solvent water structure is enhanced near the hydrophobic entity, leading to a net loss of entropy . The structural ordering of liquid water to form cages around hydrophobic solute species is explored using various experimental techniques. In this respect, the interactions of water with hydrophobic additives are also discussed in terms of the clathrate hydrate (CH) formation. CHs are inclusion compounds in which small guest molecules are confined in cages formed by hydrogen-bond networks of water molecules. In contrast with crystalline ices, an open frame of polyhedral water cages is formed in CH because of the predominance of pentagonal rings relative to hexagonal ones, and the cage is stabilized by interactions of water with guest molecules. Because of the low solubility of hydrophobic species, the development of CHs from liquid water requires a very long time, ranging from hours to days .…”
Section: Introductionmentioning
confidence: 99%
“…The ASW film formed at temperatures <70 K is characterized by a microporous structure; the effective surface area of porous ASW films has been determined from the TPD spectra of trapped N 2 molecules in the film interior. In contrast with this picture, it has been depicted that hydrophobic molecules are not simply physisorbed on the surface of ASW but are compressed and caged microscopically by the hydrogen-bonded water molecules. , The bulk properties of ASW can be modified by water-miscible polar molecules because they reduce the water activity via disruption of the water’s hydrogen-bond network. , Alcohols are known to be the most popular hydrate formation inhibitors, , but some weakly polar molecules like cyclic ethers rather act as promoters. , …”
Section: Introductionmentioning
confidence: 99%